(untitled) (Applied Biological Research, 2013)
Root mealy bug Paraputo sp. (Hemiptera: Pseudococcidae) is the most dreaded pest of mulberry (Morus sp.), in Darjeeling hills of West Bengal (India). The pest incidence recorded at monthly intervals for three consecutive years revealed that the pest population was low in December-January, increased with rise in temperature and relative humidity upto rainy season (July-August) and then gradually declined. The peak population of 50.88-52.05 plant-1 was in August. No significant variation was observed between the years in population fluctuations.